Modal Sosial Kelompok Tani Lengkuas Dalam Meningkatkan Perekonomian Masyarakat Rubaru Sumenep Madura - Rahmah Fadilatur; Ekna Satriyati (DIMENSI - Journal of Sociology, 2022)
Abstrack Farmer cluster formation is to be effort for reaching the aim and also as way to share their opinion each other and their experience each other. Indirectly farmer cluster formation is a tool of social financial capital.it is because farmer cluster formation obtains society solidarity. The important quintessence in social financial capital is not only focus on the success which fixed by the farmer cluster it self but also from each person in that cluster. As well as society at Kaleleng village which majority society’s profession is as a farmer specifically in ginger plant that from farmer cluster. But, day by day society participation is lowering and it influence to their agriculture. The aim of this writing is to give information to the readers that social financial capital which formed by farmer cluster at Kaleleng village has important role in increasing society economy. It means society participant for optimizing farmer cluster in increasing economy collectively. This research is qualitative research in descriptive analytic by using society unit analysis which has a role in farmer cluster activity.